Biosimilar Use and Switching in Belgium: Avenues for Integrated Policymaking - Barbier, Liese; Simoens, Steven; Declerck, Paul; Vulto, Arnold G.; Huys, Isabelle (Frontiers in Pharmacology, 2022)
Background: By improving the affordability and accessibility of biologicals, biosimilar competition provides important benefits to healthcare systems and patients. In Belgium, biosimilar competition is limited compared to other European markets. Whereas other countries have initiated structured biosimilar introduction or switching plans, no such framework or guiding principles are yet available in Belgium. Objective: This study aims to develop recommendations that can inform policy action in Belgium on biosimilar use, especially in the context of switch decision-making, and this by drawing from the perspectives of healthcare professionals involved in procuring, prescribing, switching and dispensing biologicals including biosimilars. Methods: This study made use of the consensus-building Nominal Group Technique, consisting of a three-step process ((i) individual grading, (ii) three structured Focus Group Discussions, (iii) final individual grading involving an expert group of Belgian healthcare professionals (physician specialists and hospital pharmacists). Results: Participants (n=13) voiced challenges with the use of biosimilars and switching in practice, and a lack of incentives to use them. Six concrete areas for policy development to support stakeholders with biosimilar use and switch decision-making were identified: (i) address stakeholder hesitations regarding (multiple) switching, (ii) provide meaningful incentives, (iii) guide healthcare professionals with product decision-making, (iv), align practical product modalities when possible, (v) involve healthcare professionals in policy making, and (vi) provide practical switch support and patient information material, particularly in the ambulatory care setting. For each area, specific consensus-based recommendations were developed. Furthermore, a set of switch management and patient communication principles was derived, including amongst others, generating buy-in from involved stakeholders prior to switching and communicating with a one-voice message. Conclusion: Without cohesive actions to reduce hurdles and without tangible benefits or steering mechanisms, changes in biosimilar use are unlikely in Belgium. To overcome this and stimulate market competitiveness, this study advances a set of concrete policy recommendations. At large, policy makers should develop an integrated policy framework, with a pro-active, best-value biological implementation roadmap that provides guidance and compelling measures to incentivize healthcare professionals to use biosimilars. Particular consideration should go to the ambulatory care setting, since drivers for biosimilar use are quasi absent in this context.